2010
DOI: 10.3928/15428877-20100929-09
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Deep Anterior Lamellar Keratoplasty (DALK): Learning Curve with Big-Bubble Technique

Abstract: DALK big-bubble technique may be a valuable procedure during transition from penetrating keratoplasty to anterior lamellar keratoplasty. It provided acceptable visual and refractive outcome even during the learning period in a variety of corneal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…The percentage of patients with CDVA > _20/40 was in keeping with previous reports showing similar results after PK (73%-91%) or DALK (72%-92%) in patients with KC. [18][19][20]24,26,[28][29][30][31][32] Both a randomized controlled trial 33 and a report from the American Academy of Ophthalmology 10 concluded that DALK is comparable to PK in terms of CDVA and refractive outcomes. On the contrary, a recent graft registry prospective cohort study has shown PK to be superior to DALK in terms of CDVA and graft survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients with CDVA > _20/40 was in keeping with previous reports showing similar results after PK (73%-91%) or DALK (72%-92%) in patients with KC. [18][19][20]24,26,[28][29][30][31][32] Both a randomized controlled trial 33 and a report from the American Academy of Ophthalmology 10 concluded that DALK is comparable to PK in terms of CDVA and refractive outcomes. On the contrary, a recent graft registry prospective cohort study has shown PK to be superior to DALK in terms of CDVA and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies showed that DALK graft survival is longer than PK at short-and medium-term follow-up, [13][14][15][16] with a more favorable cost-benefit ratio in comparison to PK. 17 On the other hand, DALK, presenting a steep learning curve, requires longer operating time than PK, 9,[18][19][20][21][22][23][24][25][26][27][28] limiting the overall diffusion of this procedure. As DALK has only recently been introduced in many tertiary centers, reports of long-term postoperative outcomes of this procedure are scarce, often including different DALK techniques and patients with various corneal diseases grouped together.…”
mentioning
confidence: 98%
“…20 In contrast, Unal and associates reported a lower rate of complications after having undertaken 40-50 DALK using the big bubble technique, and suggested that a relatively greater surgical experience may be required before success rates are improved. 17 We did not, however, find evidence to support this. In particular, we examined graft survival for individual surgeons who had performed more than 50 DALKs in the defined time period, but did not identify any learning effects.…”
Section: Despite the Potential Advantages Of Dalk Overmentioning
confidence: 53%
“…This is in contrast to the rapid uptake of endothelial keratoplasty, which in the UK now accounts for 85% of all corneal transplants undertaken for Fuchs endothelial dystrophy and pseudophakic corneal edema. Although a plateau in uptake may reflect the technical difficulties associated with DALK surgery, 17 it may also reflect the slightly better visual outcomes for patients with keratoconus undergoing PKP compared with DALK. 2,9,18 This study is based on registry data, which has both advantages and limitations.…”
Section: Despite the Potential Advantages Of Dalk Overmentioning
confidence: 97%
“…[97][98][99] When a perforation occurs, the surgeon can choose to convert to PK, or can make adjustments using intracameral air injection or patches to complete the stromal lamellar dissection without converting to PK. 29 The complication rate of microdrilling can be high, reaching 39%, even for experienced surgeons.…”
Section: Intraoperative Complicationsmentioning
confidence: 99%